Antidiabetic, anticholinergic and antioxidant activities of aerial parts of shaggy bindweed (Convulvulus betonicifolia Miller subsp.) – profiling of phenolic compounds by LC-HRMS - Zeynebe Bingol; Hatice Kızıltaş; Ahmet C. Gören; Leyla Polat Kose; Meryem Topal; Lokman Durmaz; Saleh H. Alwasel; İlhami Gulcin (Heliyon, 2021)
In order to evaluate the antioxidant activity of evaporated ethanolic extract (EESB) and lyophilized water extract (WESB) of Shaggy bindweed (Convulvulus betonicifolia Mill. Subs), some putative antioxidant methods such as DPPH· scavenging activity, ABTS•+ scavenging effect, ferric ions (Fe3+) reduction method, cupric ions (Cu2+) reducing capacity, and ferrous ions (Fe2+) binding activities were separately performed. Also, ascorbic acid, α-tocopherol and BHT were used as the standard compounds. Additionally, some phenolic compounds that responsible for antioxidant abilities of EESB and WESB were screened by liquid chromatography-high resolution mass spectrometry (LC-HRMS). At the same concentration, EESB and WESB demonstrated effective antioxidant abilities when compared to standards. In addition, EESB demonstrated IC50 values of 1.946 μg/mL against acetylcholinesterase (AChE), 0.815 μg/mL against α-glycosidase and 0.675 μg/mL against α-amylase enzymes.